Permissive role of Cdc2 activity induced from astrocytes in neurite outgrowth. (13th February 2013) - Chang, In Ae; Kwon, Ku‐Birm; Park, Yang‐Chun; Namgung, Uk
Abstract Following spinal cord injury, glial cells are recognized as major environmental factors hampering axon's regenerative responses. However, recent studies suggested that, in certain circumstances, reactive astrocytes may have a permissive role for axonal regeneration and functional recovery. Here, we report that Cdc2 activation in astrocytes is positively linked to axon growth. Cdc2 was strongly, but transiently, induced from reactive astrocytes within and around the injury cavity. Cdc2 levels in primary, non‐neuronal cells prepared from injured spinal cord were up‐regulated by extending the pre‐injury period. Cdc2‐mediated vimentin phosphorylation was strongly induced in astrocytes after long‐term culture (7 days, LTC) as compared with short‐term culture (3 days, STC). Induction levels of phospho‐vimentin in LTC astrocytes were positively associated with increased neurite outgrowth in co‐cultured dorsal root ganglion neurons. β3 integrin mRNA was induced in LTC astrocytes and activation of β3 integrin was regulated by Cdc2 activity. Furthermore, genetic depletion and pharmacological blockade experiments demonstrate that activation of Cdc2 and β3 integrin in LTC astrocytes is required for neurite outgrowth. Our data suggest that the Cdc2 pathway may play an important role in determining phenotypic expression of astrocytes such that astrocytes provide permissive environments for axonal regeneration following spinal cord injury.